Advances in application of ultrasound in meat tenderization: A review - Dong, Yixuan; Zhang, Hongzhi; Mei, Jun; Xie, Jing; Shao, Changbo (Frontiers in Sustainable Food Systems, 2022)
Tenderness could measure the eating quality of meat. The mechanism of muscle tenderization is becoming more and more critical in the past decade. Since the transforming of muscle into edible meat requires a complex physiological and biochemical process, the related tenderization of meat can be beneficial to improving the meat quality. As a non-thermal processing technology with energy-saving, environmental protection, and intense penetration, ultrasonic treatment has been widely used in the tenderizing process of meat products. In this paper, the principle of meat tenderization, the ultrasonic technology, and the application of ultrasonic technology in meat tenderization is summarized. The effect of ultrasonic technology on the tenderization of meat products is discussed from different perspectives (muscle fibers and connective tissue properties).